Determination of Sodium Sulfate Requirement for Obtaining Sodium Sulfide Content in Green Liquor at the Recovery Boiler Unit in PT XYZ North Sumatra - Donda; Paranita, Darni; Simatupang, Dimas Frananta (International Journal of Applied Research and Sustainable Sciences, 2023)
Black liquor is a residual cooking liquid containing organic chemicals utilized as fuel in the recovery boiler and inorganic chemicals that can be recovered into cooking liquid through the recovery boiler process. The recovery boiler is a specialized boiler unit used to restore black liquor by reducing sodium sulfate into sodium sulfide. The research method involved field observations, liquor content analysis, and stoichiometric calculations to determine the sodium sulfate requirement. The calculations revealed that the sodium sulfide content obtained from the recovery boiler process in green liquor was 24.428 g/l Na2O, requiring a reactive amount of 46,5225.0328 kg/day of sodium sulfate. The target sodium sulfide content in the green liquor aimed for was 18-30 g/l. The results indicated that the sodium sulfide content has met the predetermined target and can be utilized for subsequent processes.